(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In this article a challenge has been made to analysis the explore studies on significance of data mining techniques in the field of agriculture. Couple of the techniques, such as decision algorithms ID3, the CHAID algorithm, C4.5, and Cluster analysis applied in the field of agriculture was presented. Data mining in application of agriculture is a relatively new approach for forecasting / predicting of fungal diseases of agricultural crop. This article explores the applications of data mining techniques in the field of farming and similar sciences. Keywords: ID3 algorithm, CHAID algorithm, C4.5, Cluster analysis.